Culture and Evolution: A Contribution to the Renewal of Discussion? - Moraczewski, Krzysztof (Sensus Historiae, 2024)
The emergence of new discoveries and interpretations in archeology, history and ethnography suggests the revision of the already established and still taught social regularities. These regularities are still being articulated on the basis of anthropological evolutionism and neoevolutionism, regardless of any theoretical criticism. The article suggests, though, that this is also the chance for a new approach to the relation between theory of culture and biological theory of evolution, the one that avoids the traditional misunderstanding of the biological idea; a misunderstanding that led to the continuation of inherited, teleological historiosophies under the misleading name of ‘cultural evolution.’